Hey, Bruce! : an interactive book - Higgins, Ryan T. (Los Angeles : Disney/Hyperion, 2022)
Three mice guide readers on quest for a fun reading experience, with a reluctant Bruce as the star.
Ages 3-5.
Grades K-1.
Keywords: Bears -- Juvenile fiction; Mice -- Juvenile fiction; Books and reading -- Juvenile fiction; Bears -- Fiction; Mice -- Fiction; Books and reading -- Fiction; Picture books